Pengaruh Kompensasi Dan Pengembangan Karir Terhadap Kinerja Pegawai Di Badan Pengelola Keuangan Aset Daerah (BPKAD) Kota Cimahi - Ramadanty, Elsa Fathia; Adji, Widwi Handari (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2023)
This study describes the effect of Compensation and Career Development on Employee Performance in government agencies, namely the Cimahi City Regional Asset Financial Management Agency. This type of research uses a descriptive method with a quantitative approach by using primary data in the form of questionnaires and secondary data in the form of documents, describing data collected numerically or using statistical tools to study certain populations or samples to test. This study aims to analyze the effect of compensation and career development on employee performance at BPKAD Cimahi City. The research was conducted using survey methods and file data collection was carried out through questionnaires distributed to BPKAD Cimahi City employees. The collected data were analyzed using multiple regression method. Judging from the results above, it is known that compensation and career development have a significant effect on the performance of BPKAD employees. Partially (t) the variables compensation (X1) and career development (X2) have a positive and significant effect on employee performance (Y) with t calculate compensation (X1) 1.603 with a significant value of 0.119 (>0.05) and career development (X2) have a calculated t value of 3.875 with a significance value of 0.000 (<0.05). Simultaneously from the output it can be seen that F is calculated at 6.266 with a significance/probability level of 0.005 <0.05